Dynamics of endothelial dysfunction, nephropathic and dyslipidemic disorders in patients with insufficient glycemic compensation of type 2 diabetes mellitus during 1 year of application of angiotensin II receptor antagonists for hypertension correction. - Pertseva, N. O. (Medicni Perspektivi, 2014)
The purpose of this study was to determine the dynamics of endothelial dysfunction, nephropathic and dyslipidemic disorders in patients with an insufficient compensation of type 2 diabetes mellitus and hypertension in the correction of blood pressure using angiotensin II receptor antagonists for 1 year. In patients with type 2 diabetes mellitus with insufficient compensation of hyperglycemia on the background of the standard treatment of hypertension in the normalization of glycated hemoglobin in 61.9% of patients, partial reduction of markers of endothelial dysfunction, regression of microalbuminuria in 32.3% of patients, as well as the normalization of concentrations of low density lipoproteins cholesterol and triglycerides occur after 1 year of treatment. Antihypertensive treatment of patients with insufficient compensation of hyperglycemia using angiotensin II receptor antagonists significantly more effective than standard treatment rule tactics by the influence on development of endothelial dysfunction on the background of normalization of nephropathic and dyslipidemic disorders. Within one year of treatment of hypertension with angiotensin II receptor antagonists concentrations of endothelin-1 and thrombomodulin reduced more than doubled relative to the initial values, the level of von Willebrand factor decreases by 67.4% (p<0,05). In this group, the level of glycated hemoglobin returns to the norm in 73.3% of patients, regression of microalbuminuria is achieved in 54.7% of patients.